A phase II study of Givinostat in combination with hydroxycarbamide in patients with polycythaemia vera unresponsive to hydroxycarbamide monotherapy. (10th April 2013) - Finazzi, Guido; Vannucchi, Alessandro M.; Martinelli, Vincenzo; Ruggeri, Marco; Nobile, Francesco; Specchia, Giorgina; Pogliani, Enrico Maria; Olimpieri, Odoardo Maria; Fioritoni, Giuseppe; Musolino, Caterina; Cilloni, Daniela; Sivera, Piera; et al.
Summary Givinostat, a histone‐deacetylase inhibitor (HDACi), inhibits proliferation of cells bearing the JAK2 V617F mutation and has shown significant activity with good tolerability in patients with chronic myeloproliferative neoplasms (MPN). In this multicentre, open‐label, phase II study, 44 patients with polycythaemia vera (PV), unresponsive to the maximum tolerated doses (MTD) of hydroxycarbamide (HC), were treated with Givinostat (50 or 100 mg/d) in combination with MTD of HC. The European LeukaemiaNet response criteria were used to assess the primary endpoint after 12 weeks of treatment. Complete or partial response was observed in 55% and 50% of patients receiving 50 or 100 mg of Givinostat, respectively. Control of pruritus was observed in 64% and 67% of patients in the 50 and 100 mg groups, respectively. The combination of Givinostat and HC was well tolerated: eight patients (18%) discontinued, four in each treatment arm; grade 3 adverse events were reported in one patient (4·5%) in each treatment arm. The combined use of Givinostat and HC was safe and clinically effective in HC‐unresponsive PV patients.